2020
DOI: 10.1038/s41598-020-66522-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of lipid domains by two Gb3-binding lectins

Abstract: The two lectins LecA from Pseudomonas aeruginosa and the B-subunit of Shiga toxin from Shigella dysenteriae (StxB) share the glycosphingolipid globotriaosylceramide (Gb3) as receptor. Counterintuitively, we found that LecA and StxB segregated into different domains after recognizing Gb3 at the plasma membrane of cells. We hypothesized that the orientation of the carbohydrate head group of Gb3 embedded in the lipid bilayer differentially influences LecA and StxB binding. To test this hypothesis, we reconstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…Of note, LecA and StxB both bind to Gb3, but partially localize to different membrane domains [ 23 ] and exhibit distinct trafficking routes [ 106 ]. In our analysis, no clear difference in binding behavior to Gb3 species of LecA in comparison to StxB was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, LecA and StxB both bind to Gb3, but partially localize to different membrane domains [ 23 ] and exhibit distinct trafficking routes [ 106 ]. In our analysis, no clear difference in binding behavior to Gb3 species of LecA in comparison to StxB was observed.…”
Section: Discussionmentioning
confidence: 99%
“…These domains are enriched in GSLs, cholesterol and glycosylphosphatidylinositol (GPI)-anchored proteins and serve as sorting and signaling platforms [ 24 26 ]. Due to the high saturation level of the fatty acyl chains of Gb3, the lipid is preferentially but not exclusively located in lipid rafts [ 23 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In synthetic and cell-derived membrane systems, glycosphingolipids with saturated fatty acyl chains incorporate in Lo, whereas GSLs with unsaturated chains prefer Ld domains. This was shown for GSLs monosialotetrahexosylganglioside (GM1), and globotriaosylceramide (Gb3) [32,68,[73][74][75]. Furthermore, introduction of a fluorophore can induce the loss of specificity to Lo domains, and similar to the phospholipids, introduction of a flexible spacer between the fluorescent moiety and GSL headgroup can improve partitioning to Lo [68].…”
Section: Fluorescence To Study Phase Separationmentioning
confidence: 95%
“…The globotriaosyl ceramide Gb 3 , also referred to as P K blood group antigen and CD77 (Johannes and Römer 2010 ), is the major receptor lipid for a number of lectins. Just recently, Römer and co-workers have shown that Gb 3 segregates into different domains at the plasma membrane of cells, which leads to a different binding behaviour of Shiga toxin compared to the lectin LecA from Pseudomonas aeruginosa (Schubert et al 2020 ). The receptor lipid is composed of the trisaccharide α-D-galactose-(1 → 4)-β-D-galactose-(1 → 4)-β-D-glucose, bound via an acetal to a sphingosine moiety.…”
Section: Introductionmentioning
confidence: 99%